An Extraterritorial Privacy Zone? : Dutch Protestants and their Embassy Chapel in Early Modern Portugal - Krijger, Tom-Eric (TSEG - The Low Countries Journal of Social and Economic History, 2021)
The Protestant Reformation led to a radical redrawing of the map of Europe, severely affecting international relations. An important consequence of Protestantism was the emphasis on the private dimension of religious practices, as it did away with clerical intermediaries and instead put the focus on the direct relationship between God and the believer. In this context, to facilitate diplomatic traffic between Catholic and Protestant countries, ambassadors came to enjoy the so-called Right of Chapel, allowing them to create a private place of worship and have a private chaplain at their ambassadorial residences. This right was explicitly included in two treaties that the Kingdom of Portugal and the Dutch Republic concluded with each other in the mid-seventeenth century. However, the two parties to the treaties had starkly different understandings of what was meant by ‘private’. Both of these treaties granted Dutch citizens in Portugal freedom of conscience in their own houses, but the contrasting interpretations of what ‘private’ actually meant for the Dutch and for the Portuguese resulted in serious disagreement about the exact scope of these religious rights.